Analysis of Students' Learning Motivation in Calculus on the Usage of Learning Video Media during the Covid-19 Pandemic - Sumargiyani; Ardi Dwi Susandi; Nur Robiah Nofikusumawati Peni (Department of Mathematics Education University of Muhammadiyah Malang, 2022)
The Covid-19 pandemic has changed the process of teaching-learning activities from offline to online. Implementing this activity causes a lack of motivation and self-confidence for undergraduate students. This study describes undergraduate students' learning motivation for using video media in integral calculus lectures for integral application materials to calculate the shape area during the Covid-19 pandemic. This research is quantitative descriptive research. The research participants were 23 undergraduate students from Ahmad Dahlan University in mathematics education. Data was collected by distributing questionnaires via Google Form consisting of 32 statements with five alternative answer choices and eight questions about learning motivation when utilizing learning video media. The analytical technique used was quantitative descriptive analysis. The results show that learning video media effectively motivates student learning in integral calculus during the Covid-19 pandemic with an average percentage result of 90.625% with very high criteria.